Analysis of Students' Mathematical Communication in Drawing Graphs of Multivariable Functions - Tyaningsih, Ratna Yulis; Arjudin, Arjudin; Hikmah, Nurul (Indonesian Journal of Science and Mathematics Education, 2020)
Mathematical communication competencies help students to convey mathematical ideas orally and in writing. The purpose of this study was to analyze students' communication skills in drawing graphs of multivariable functions in advanced calculus courses. This type of research is qualitative with descriptive methods. The subjects in this study were 28 students of Mathematics Education class 4B. This study used a stratified random sampling technique to obtain 3 students consisting of high, medium, and low mathematics competencies. The data collection instruments used were the competency mapping test, evaluation test, and interview guidelines. The results of this study are (1) students with high competence excel at writing and making mathematical models, (2) students with moderate competence have advantages in three stages, but there are few errors in applying the agreement, (3) students with low competence make mistakes at the third stage due to wrong in formulating problems and designing problem-solving strategies.